1. преобразуйте в многочлен: а) (b – 5)2; в) (6x – y)(6x + y); б) (4a + c)2; г) (p 2 + q)(p 2 – q). 2. разложите на множители: а) x2 – 0,81; б) a 2 – 6a + 9. 3. найдите значение выражения (y + 5)2 – (y – 5)(y + 5) при y = –4,7. 4. выполните действия: а) 4(5a – b)(5a + b); в) (x + 6)2 – (x – 6)2. б) (c 4 + d 3) 2; 5. решите уравнение: а) (3х – 2)2 – (3х – 1)(3х + 1) = –2x; б) 25a2 – 81 = 0.
(6x-y)(6x+y)=36x^2+6xy-6xy-y^2=36x^2-y^2
(4a+c)^2=16a^2+2*4a*c+c^2=16a^2+8ac+c^2
(p^2+q)(p^2-q)=p^4-p^2q+p^2q-q^2
Остальное делай сама